Die Landschaft der Regionalentwicklung: Wie flexibel ist der Landschaftsbegriff? - Hokema, Dorothea (Raumforschung und Raumordnung | Spatial Research and Planning, 2009)
The discussion about cultural landscapes during the past few years is amongst others a discussion about a shift in the interpretation of the term landscape from the traditional ideal of idyllic cultural landscapes to a more pragmatic and up-to-date-definition. This article compares the so-called “narrow” term to a “wider” term of landscape and surveys how these terms appear in regional-park concepts. As a result, possibilities and constraints of “widening” the term landscape are presented.
Keywords: land-use planning; Landscape; Regional development; Regional Park; Urban sprawi